Corporate social responsibility and customer retention: evidence from the telecommunication industry in Ghana. Issue 1 (6th October 2020) - Afiuc, Otto; Bonsu, Samuel K.; Manu, Franklyn; Knight, Casey Brett; Panda, Swati; Blankson, Charles
Abstract : Purpose: Using social exchange theory as a contextual backdrop, this study aims to better understand how corporate social responsibility (CSR) can contribute to customer retention (CR). A conceptual framework is developed to illustrate the proposed relationship and the influence of mediating factors. The telecommunication industry in Ghana is used to operationalize the conceptual framework. Design/methodology/approach: Qualitative and quantitative data were collected through face-to-face interviews with CSR managers and through a structured questionnaire. The data were analyzed using qualitative analysis and structural equation modeling. Findings: Findings suggest that CSR, corporate image and service quality have significant relationships with both corporate image and CR. Corporate image also mediates the relationship between CSR, customer value and service quality with that of CR. The authors also find that CSR strengthens the relationship between customer value and service quality with that of corporate image, which subsequently leads to enhanced CR. Originality/value: Thus far, the mediating variables that help explain and predict the relationship between CSR activities and CR have been overlooked in the extant literature. The results of this study will help fill a critical knowledge gap in marketing and CSR literature.